Faecal metabolite deficit, gut inflammation and diet in Parkinson's disease: Integrative analysis indicates inflammatory response syndrome. Issue 1 (1st January 2023) - Augustin, Aisha; Guennec, Adrien Le; Umamahesan, Chianna; Kendler‐Rhodes, Aidan; Tucker, Rosalind M.; Chekmeneva, Elena; Takis, Panteleimon; Lewis, Matthew; Balasubramanian, Karthik; DeSouza, Neville; Mullish, Benjamin H; Taylor, David; et al.
ABSTRACT: Background: Gut‐brain axis is widely implicated in the pathophysiology of Parkinson's disease (PD). We take an integrated approach to considering the gut as a target for disease‐modifying intervention, using continuous measurements of disease facets irrespective of diagnostic divide. Methods: We characterised 77 participants with diagnosed‐PD, 113 without, by dietary/exogenous substance intake, faecal metabolome, intestinal inflammation, serum cytokines/chemokines, clinical phenotype including colonic transit time. Complete‐linkage hierarchical cluster analysis of metabolites discriminant for PD‐status was performed. Results: Longer colonic transit was linked to deficits in faecal short‐chain‐fatty acids outside PD, to a 'tryptophan‐containing metabolite cluster' overall. Phenotypic cluster analysis aggregated colonic transit with brady/hypokinesia, tremor, sleep disorder and dysosmia, each individually associated with tryptophan‐cluster deficit. Overall, a faster pulse was associated with deficits in a metabolite cluster including benzoic acid and an imidazole‐ring compound (anti‐fungals) and vitamin B3 (anti‐inflammatory) and with higher serum CCL20 (chemotactic for lymphocytes/dendritic cells towards mucosal epithelium). The faster pulse in PD was irrespective of postural hypotension. The benzoic acid‐cluster deficit was linked to (well‐recognised) lower caffeine and alcohol intakes, tryptophan‐cluster deficit to higher maltose intake. Free‐sugar intake was increased in PD, maltose intake being 63% higher ( p = .001). Faecal calprotectin was 44% (95% CI 5%, 98%) greater in PD [ p = .001, adjusted for proton‐pump inhibitors ( p = .001)], with 16% of PD‐probands exceeding a cut‐point for clinically significant inflammation compatible with inflammatory bowel disease. Higher maltose intake was associated with exceeding this calprotectin cut‐point. Conclusions: Emerging picture is of (i) clinical phenotype being described by deficits in microbial metabolites essential to gut health; (ii) intestinal inflammation; (iii) a systemic inflammatory response syndrome. Abstract : A marker of intestinal inflammation was 44% greater in Parkinson's disease, exceeding a cut‐point for inflammatory bowel disease in 16%. It was associated with a higher maltose and sucrose intake. The emerging picture is of systemic inflammatory response consequent on intestinal inflammation, clinical phenotype being described by deficits in faecal metabolites essential to gut health.